Effectiveness of Drainage Networks on Floods in Calabar Metropolis, Nigeria - Emmanuel, Efobe NDOMA; Usman, Mashkura Ahmed1; Saidu, IDRIS1; Nenpanmun ,Temwa Molus; Wali, Elekwachi; Stephen ,Hemba (Journal of Geography Meteorology and Environment, 2020)
The study examined the effects of drainage networks on floods in Calabar metropolis. The rapid increase in urbanization without corresponding infrastructures in the city of Calabar has led to increased incidences of flood as the available drainage channels cannot contend with the volume of storm water. In view of this, the study established gauging stations for the measurement of drainage run off using measuring steel tape. The volume of flood water was determined using stop watch method (Velocity of flow) and copies of questionnaire were administered to 400 households proportionally to the seven sample units. Results from the work revealed that the frequency of flood is compounded with much intensity as over 59% of the sampled population agreed that flood is very high in Calabar. The study also revealed that the drainage were very narrow and shallow and contributed to the frequent floods in the city. The incessant flood often led to water inundating compounds (64.5%), preventing people from going out (11.25%), distortion of the scenic beauty of the environment (6.25%) and landslide (4.75%). Based on these findings, the study recommended that since Calabar is located in a tropical zone characterized by heavy rainfall, the government should take proactive measure to mitigate storm water. The present drainage systems should be cleared by the people on a regular basis to allow for a free flow of storm water.
Keywords: Drainage; network; urbanization; rainfall